A Study of Alternative Catalysts and Analysis Methods for Biodiesel Production - Tirla, Cornelia; Smith, Rachel B.; Dooling, Thomas; Kingsbury, Nathaniel; McKee, Christopher; Panter, Rebecca; Allen, Arieana Van (European Scientific Journal, ESJ, 2017)
This project aims to develop a cost efficient process for biodiesel production and can be divided in three main components: 1) production of biodiesel from a variety of fuel stocks using liquid morpholine as catalyst; 2) production of biodiesel using a homogeneous phase transfer catalyst; and 3) development of a method for using Infrared Spectroscopy (IR) to determine the extent of conversion of oil to biodiesel. The production of biodiesel from various fuel stocks in the presence of methanol using liquid morpholine as catalyst reduces the problems related to purification of the biodiesel since morpholine can be recovered by distillation. Furthermore the use of two homogeneous phase transfer catalyst, tetramethylammonium hydroxide (TMAH) and choline hydroxide (CH), was evaluated. The advantage of using these catalysts is that it allows for a better separation between the fuel and glycerin, thus additionally simplifying the purification procedure. Finally, this project endeavored to develop a way to use FT-IR to determine the purity of biodiesel samples obtained since FT-IR is faster and more readily available than the standard method of gas chromatographic analysis. For educational applications, a calibration curve was created by comparing data on the purity of biodiesel samples obtained from the GC-FID analysis to the ratio of the absorbances at 1197 cm-1 to 1166 cm-1 from the FT-IR spectrum. For field application, a similar method was developed using a portable IR spectrometer. The data collected gave a good linear fit for % purity of the samples versus absorbance ratio.